Recent progress of polydopamine nanoparticles as advanced antimicrobial nanomaterials - Guzman-Sanchez, Sandra; Patel, Niketan; Rosado, Alexandre Soares (Frontiers in Bioengineering and Biotechnology, 2025)
The global rise of antimicrobial resistance has driven the search for novel antimicrobial strategies with higher effectiveness than common antibiotics. Among various solutions, polydopamine nanoparticles (PDA NPs) have gained widespread attention owing to their biocompatibility, functional versatility, and responsiveness to environmental stimuli. This review summarizes recent advances in the synthesis, functionalization, and antimicrobial applications of PDA NPs, highlighting their potential as smart nanomaterials. PDA NPs exhibit intrinsic antimicrobial activity, large drug delivery capabilities, and excellent photothermal properties. Moreover, they can potentially eradicate biofilms; can be synergistically combined with other entities such as metal ions, antimicrobial peptides, and Fenton-like catalysts; and can provide in vivo models of bacterial infection. Despite these advantages, the widespread use of PDA NPs is limited by low synthesis reproducibility, insufficient accurate characterization, and lack of comprehensive biocompatibility assessment. Resolving these challenges is essential for fully comprehending and using the potential of PDA-based antimicrobial platforms. This review aims to explain the current landscape of PDA-based nanoformulations and to inspire future research toward clinically viable PDA-based nanoformulations.